Palatability Test on Rice Straw, Grass and Sorghum Silage for Cattle in Cambodia - Mach Din; Koemseang Nhoung; Tatik Suteky; Endang Sulistyowati; Pao Srean (AGRITROPICA : Journal of Agricultural Sciences, 2022)
Feed is a constraint of cattle production in Cambodia. Rice straw, fresh grass, and sorghum silage were used to assess palatability for cattle feeding. Five cattle were used for the palatability test over seven days. The results showed the feed intake of fresh grass was greater than fresh grass or Sorghum silage. No difference in preference index between the rice straw and sorghum silage for the amount of feed intake. Sorghum silage can be used as alternative to rice straw for the improvement of cattle production in Cambodia.